A Novel Amino Acid Composition Ameliorates Short-Term Muscle Disuse Atrophy in Healthy Young Men - Holloway, Tanya M.; McGlory, Chris; McKellar, Sean; Morgan, Adrienne; Hamill, Mike; Afeyan, Raffi; Comb, William; Confer, Scharmen; Zhao, Peng; Hinton, Mark; Kubassova, Olga; Chakravarthy, Manu V.; et al. (Frontiers in Nutrition, 2019)
Skeletal muscle disuse leads to atrophy, declines in muscle function, and metabolic dysfunction that are often slow to recover. Strategies to mitigate these effects would be clinically relevant. In a double-blind randomized-controlled pilot trial, we examined the safety and tolerability as well as the atrophy mitigating effect of a novel amino acid composition (AXA2678), during single limb immobilization. Twenty healthy young men were randomly assigned (10 per group) to receive placebo AXA2678 or an excipient- and energy-matched non-amino acid containing placebo (PL) for 28d: days 1-7, pre-immobilization; days 8-15, immobilization; and days 16-28 post-immobilization recovery. Muscle biopsies were taken on d1, d7 (immobilization start), d15 (immobilization end), and d28 (post-immobilization recovery). Magnetic resonance imaging (MRI) was utilized to assess quadriceps muscle volume (Mvol), muscle cross-sectional area (CSA), and muscle fat-fraction (FF: the fraction of muscle occupied by fat). Maximal voluntary leg isometric torque was assessed by dynamometry. Administration of AXA2678 attenuated muscle disuse atrophy compared to PL (p<0.05) with changes from d8 to d15 in PL: ΔMvol = -2.4 ± 2.3% and ΔCSA = -3.1% ± 2.1%, both p<0.001 versus zero; against AXA2678: ΔMvol: -0.7 ± 1.8% and ΔCSA: -0.7 ± 2.1%, both p>0.3 versus zero; and p<0.05 between treatment conditions for CSA. During immobilization, muscle FF increased in PL but not in AXA2678 (PL: 12.8 ± 6.1%, AXA2678: 0.4 ± 3.1%; p<0.05). Immobilization resulted in similar reductions in peak leg isometric torque and change in time-to-peak (TTP) torque in both groups. Recovery (d15 to d28) of peak torque and TTP torque was also not different between groups, but showed a trend for better recovery in the AXA2678 group. Thrice daily consumption of AXA2678 for 28d was found to be safe and well-tolerated. Additionally, AXA2678 attenuated atrophy and attenuated accumulation of fat during short-term disuse. Further investigations on the administration of AXA2678 in conditions of muscle disuse are warranted.